Potensi penurunan konsumsi energi di DKI Jakarta dengan menggunakan rumah ramah lingkungan - Sasono, Bagus Arifianto; Febraldo, David; Susanti, Lily (Institute for Advanced Social, Science, and Sustainable Future, 2024)
Background: With the rapid development of DKI Jakarta, it is estimated that the energy demand will increase. With the current trend of environmentally friendly housing concepts, a decrease in energy consumption is expected if people are willing to switch to eco-friendly homes or use eco-friendly components such as LED lights, water-saving showers, or solar panels. There are several inhibiting factors for people to use eco-friendly homes, including willingness to pay, preferences regarding eco-friendly homes, reluctance towards eco-friendly homes, and environmental awareness. The aim of this research is to understand the understanding, preferences, and reluctance of the public regarding eco-friendly homes, analyze the potential of DKI Jakarta residents to move to eco-friendly homes or their components, and analyze the potential decrease in energy usage in DKI Jakarta through the use of eco-friendly homes and their components. Methods: This research was conducted using a quantitative approach with qualitative and quantitative methods. The analysis method in this study is descriptive analysis and energy consumption reduction potential calculation. Findings: The results of this study show that the majority of DKI Jakarta residents already understand eco-friendly homes and have preferences to move despite some reluctance factors. Conclusion: Moreover, the majority of DKI Jakarta residents (more than 50%) have the potential to use eco-friendly homes and switch to water, electricity, and construction material-saving components. The potential decrease in energy consumption in DKI Jakarta in the future is predicted to reach over 15% if moving to eco-friendly homes altogether and potentially reducing energy needs by more than 15% in water consumption and over 30% in electricity consumption. These results are obtained by combining the desire to move and the potential energy savings from each component.